5-Hydroxyethyl-3-tetradecanoyltetramic acid represents a novel treatment for intravascular catheter infections due to Staphylococcus aureus. (19th December 2016) - Zapotoczna, Marta; Murray, Ewan J.; Hogan, Siobhan; O'Gara, James P.; Chhabra, Siri R.; Chan, Weng C.; O'Neill, Eoghan; Williams, Paul
Abstract : Objectives: Biofilm infections of intravascular catheters caused by Staphylococcus aureus may be treated with catheter lock solutions (CLSs). Here we investigated the antibacterial activity, cytotoxicity and CLS potential of 5-hydroxyethyl-3-tetradecanoyltetramic acid (5HE-C14-TMA) compared with the related compounds 3-tetradecanoyltetronic (C14-TOA) and 3-tetradecanoylthiotetronic (C14-TTA), which are variants of quorum sensing signalling molecules produced by Pseudomonas aeruginosa . Methods: Antibacterial activity and mechanism of action of 5HE-C14-TMA, C14-TOA and C14-TTA were determined via MIC, bacterial killing, membrane potential and permeability assays. Susceptibility of S. aureus biofilms formed in the presence of plasma in vitro was investigated, MTT cytotoxicity testing was undertaken and cytokine release in human blood upon exposure to 5HE-C14-TMA and/or S. aureus biofilms was quantified. The effectiveness of 5HE-C14-TMA as CLS therapy in vivo was assessed using a rat intravascular catheter biofilm infection model. Results: MICs of 5HE-C14-TMA, C14-TOA and C14-TTA ranged from 2 to 4 mg/L. 5HE-C14-TMA and C14-TTA were bactericidal; all three compounds perturbed the staphylococcal membrane by increasing membrane permeability, depolarized the transmembrane potential and caused ATP leakage. Cytotoxicity and haemolytic activity were compound and target cell type-dependent. 5HE-C14-TMA reduced S. aureus biofilm viability in a dose-dependent manner in vitro and in vivo and did not trigger release of cytokines in human blood, but inhibited the high levels of IL-8 and TNF-α induced by S. aureus biofilms. Conclusions: 5HE-C14-TMA, C14-TOA and C14-TTA are membrane-active agents. 5HE-C14-TMA was the most potent, eradicating S. aureus biofilms at 512–1024 mg/L both in vitro and in vivo as a CLS.